Meningkatkan Pemahaman Belajar Peserta Didik dalam Desain Intruksional Berbasis Daring di Sekolah Dasar Negeri Pengakalan 1 - Ina Magdalena; Melanis Melanis; Yulianti Dewi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
Based on the results of the research carried out shows an increased student understanding in online learning. Increased learning involves postif on the understanding of students who are experiencing the ability to learn using online systems. The corona virus' online learning initially affected the languishing economic world, but now its effects are felt by the world of education as well. The policy taken by many countries including Indonesia includes liberalizing all educational activities, leading governments and associated institutions to create alternative educational processes for both student and student who are unable to carry out the education process in education institutions. The purpose of research is to identify the content of class iii learning models during the pandemic. Qualitative research with literature methods and interview/observation methods. Literature study isa study that is used in collecting information and data with the help of a wide range of materials available in libraries such as documents, books, magazines, history stories, news stories, and so on. The location and research subject are class 3, base 1 students to be conducted in January 2021.